273 Phase i study of LioCyx-M, autologous hepatitis B virus (HBV)-specific T cell receptor (TCR) T-cells, in recurrent HBV-related hepatocellular carcinoma (HCC) post-liver transplantation. (9th November 2020) - Chen, Wenjie; Cheng, Jintao; Zheng, Xiaofang; Yang, Fan; Fam, Royce; Koh, Sarene; Wai, Lu-En; Wang, Tingting; Bertoletti, Antonio; Zhang, Qi
Abstract : Background: LioCyx-M is an immunotherapeutic product based on autologous T cells transiently modified with in vitro transcribed mRNA encoding HBV-specific T-cell receptors (TCR). We have previously shown, in a compassionate setting, the ability of LioCyx-M cells to recognize and lyse hepatocellular carcinoma (HCC) expressing HBV antigens derived from HBV-DNA integration in patients with HCC recurrence post-liver transplant. 1 Here, we report our phase I study aimed to determine the feasibility, safety and preliminary efficacy of LioCyx-M in recurrent HBV-related HCC post-liver transplantation Methods: Eligible patients with HBsAg-positive recurrent HCC as well as HLA-matched to selected TCRs were enrolled in this study. All patients underwent leukapheresis prior to treatment and peripheral blood mononuclear cells (PBMC) were collected for LioCyx-M manufacturing. During the 1st treatment cycle, patients received 4 escalating doses of 1×10 4 cells/kg, 1×10 5 cells/kg, 1×10 6 cells/kg, 5×10 6 cells/kg bodyweight (BW) intravenously every 7 days. Adverse events were evaluated by Common Terminology Criteria for Adverse Events Version 4.0. In the second treatment cycle, one infusion of LioCyx-M at dose of 1–5 × 10 6 cells/kg BW was intravenously administrated every 7 days for 4 weeks. The anti-tumour efficacy of LioCyx-M was evaluated per RECIST 1.1 criteria and survival was followed-up during the study. Results: Six patients were enrolled, with a median age of 35.5 (range: 28 - 47). These patients received a median number of 6.5 doses of LioCyx-M therapy (range: 4 - 12). Only fever was observed as treatment-related AEs. Grade 1 fever was observed at dose levels of 1 × 10 4 cells/kg BW (n=1) and 1–5 × 10 6 cells/kg BW (n=3) respectively. No cytokine release syndrome- and neurotoxicity-like AEs were observed. Out of 4 patients evaluable for tumor response, the median of time to progression was at 1.3 months (range: 1.2 - 1.6 months). The median overall survival was 14 months (range: 4 - 22 months). At data cutoff (30 April 2020), one patient was still alive and 5 were deceased. Conclusions: Our data showed that multiple infusions of LioCyx-M are well tolerated at all dose levels administrated in recurrent HCC post liver transplantation, with no adverse effect to the transplanted liver. This calls for further assessment in a Phase 2 study. Acknowledgements: Funding: Lion TCR. Trial Registration: NCT02719782 Ethics Approval: The study was approved by Sun Yat-Sen Third Affiliated Hospital's Ethics Board, approval number [2015]2-157. Reference: Tan AT, Yang N, Lee Krishnamoorthy T, et al. Use of Expression Profiles of HBV-DNA Integrated Into Genomes of Hepatocellular Carcinoma Cells to Select T Cells for Immunotherapy. Gastroenterology 2019;156(6):1862–1876.e9.